On the impact of nuclear fusion power plants deployment on selected critical materials consumption - D.N. Dongiovanni; Y. Melese; F. Gracceva; C. Bustreo; A. von Müller (Energy Strategy Reviews)
Nuclear fusion is one of the possible energy supply technologies that can meet the demand of low-carbon energy. In fact, as an energy technology, it has the potential to supply significant amounts of energy from small fuel quantities without any emission of greenhouse gases. Fusion technology development efforts are currently ongoing in Europe within a roadmap oriented towards fusion adoption and global market integration in the second half of the century.Nuclear fusion is commonly considered a sustainable technology in terms of resources, given the abundance of raw materials to be used as “fuel” (namely, deuterium and lithium). However, beside lithium which is indeed experiencing a phase of great exploitation in the electric vehicle sector, other key materials are deemed crucial for the deployment at large scale of such technology. Specifically, they are beryllium and lead, required for tritium breeding process; tungsten for plasma facing material; tantalum for functional impurities in steel; niobium for Superconducting Magnets; helium for cooling and for fuel cycle. All these materials have been selected in literature as “critical raw materials” for fusion.An analysis of the possible impact of nuclear fusion power plants penetration in the energy market in terms of material resources consumption is proposed in this paper. With this goal, an estimation of the demand of fusion critical materials for building and operating a fusion power plant (FPP) based on the European baseline fusion reactor concept is presented. The possible role of fusion critical material demand by concurrent technology is also addressed as well as the potential role of material re-use/recycling in support of primary production to cover the corresponding material demand. The estimates of FPP material demand based on recent fusion EU DEMO reactor design are projected over time according to a plausible range of energy market fusion shares. Finally, projections of long-term global demand for non-fusion applications are presented for comparison and coupling with fusion-driven material demand. Criticalities emerge mostly on Be and Li with respect to FPP deployment. The first is scarce and primary production is low with respect to FPP expected demand. Criticalities on lithium emerge from the expected high concurrent demand from non-fusion applications and the need of enrichment in 6Li.